4-Nitroaniline–2,4,6-trimethoxybenzaldehyde (1/1) - Abdullah, Asiri M.; Salman, Khan A.; Tan, Kong Wai; Ng, Seik Weng (International Union of Crystallography, 2010)
In the title co-crystal, C6H6N2O2.C10H12O4, the two components are held together by an N—H[cdots, three dots, centered]Oaldehyde hydrogen bond. Adjacent co-crystals are linked by weaker N—H[cdots, three dots, centered]Onitro hydrogen bonds, forming a linear chain. The two aromatic rings of the components are aligned at 75.2 (1)°. The crystal studied was a non-merohedral twin with a 24% minor component.